In vitro digestibility of starch in sorghum differing in endosperm hardness and flour particle size - Xu, Xiaoli (Kansas State University, 2008)
In vitro digestibility of starch in sorghum grains differing in endosperm hardness and flour particle size was assayed by an Englyst resistant starch (RS) method. The starch digestibility increased as the particle size of flour decreased, but no significant difference in starch digestibility was observed among sorghum flours milled from grains with different hardness. To further understand the digestion of starch in sorghum, the effects of protein on starch digestion and amylose content in starch were determined. pH value was a factor affecting protein digestion since protein digestibility was higher at pH 2.0 than that at pH 1.3. Protein hydrolysis increased with time of pepsin treatment, leading to an increased starch digestion. RS content was 10.61-29.54% in native sorghum flours and 8.47-26.28% in isolated sorghum starch. The amounts of [Gamma]-kafirins extracted increased with time of pepsin treatment while [Alpha]- and [Beta]-kafirins decreased. The starch in sorghum flour with median hardness had a higher amylose content (23.9%) than the starch in hard and soft flours (~21%), which gave lower starch digestibility. Protein digestibility decreased after cooking while starch digestibility increased. Sulfhydryl groups decreased after cooking, indicating that disulfide bonds formed between protein molecules and may have formed a barrier for enzymes to access and digest starch. Confocal laser scanning microscopy (CLSM) showed that the protein matrix was less evident after pepsin treatment. As a result, starch digestion increased after protein matrix was removed.
Keywords: sorghum; starch; digestion; in vitro; Agriculture, Food Science and Technology (0359); Chemistry, Biochemistry (0487)